Extracting Frame-Semantics Knowledge using Lattice Theory - Valverde-Albacete, Francisco J. (J Logic Computation, 2008)
In this article, we introduce a new representation based on lattice theory for lexical data from a lexical-database embodying the frame-semantic approach to language description, FrameNet. We present proof of the abundance of Concept Lattices as proposed in Formal Concept Analysis both in the theory of frames and in its present-day incarnation, the FrameNet resource, by constructing several types of these. We further argue for the adequacy of such lattices in representing linguistic data with contributions that range from data-visualization to the fine-tuning of some frame-theoretical concepts. We argue finally that FrameNet is better thought of as being a lexical resource rather than an ontology, but we make the case throughout the article for Concept Lattices being a linguistically adequate, formally effective intermediate representations from which knowledge representation languages may draw knowledge-rich, linguistic facts from FrameNet at their convenience. 10.1093/logcom/exm069
Keywords: frame semantics; kr; lattice